Length-weight, maturity, and condition factor of torpedo scads (Megalaspis cordyla Linnaeus, 1758) in the Java Sea, Indonesia - Dian Oktaviani; Eko Prianto; Duto Nugroho (Society for Indonesian Biodiversity, 2020)
Abstract. Oktaviani D, Priyanto E, Nugroho D. 2020. Length-weight, maturity, and condition factor of torpedo scads (Megalaspis cordyla Linnaeus, 1758) in the Java Sea, Indonesia. Biodiversitas 21: 1527-1534. The Java Sea comprises the most extensive ecosystem with high pressure on the biodiversity of marine fish species in Indonesia. Small pelagic fish is the main target among marine fish species in this area for decades to fulfill the need for animal protein for human consumption. Torpedo scads (Megalaspis cordyla Linnaeus, 1758) locally called as tetengkek is one of the common species caught in small pelagic seiners fisheries in the area. The significant increasing trend of annual fish landing could lead to unsustainable long-term harvesting. This study was performed to support baseline information on the biological characteristics of Torpedo scads. Measurements on length, weight, sex, maturity, and gonad weight are the main database that collected from February to December 2017 in the Tegal fishing port, north coast of central Java. A total of 2139 specimens were available for monthly length-frequency measurements, and 601 specimens among them specifically observed for length-weight, sex, maturity stage, and their gonad weight. The result showed that fish caught within a range of 16.0-35.4 cmFL and weight of 40-570 g. The length-weight relationship tends to be isometric with the equation of L = 7.e-03 W3.1511. The male and female ratio at 1.07: 1.0 with most of the fish caught at an immature stage (77% of males and 63% of females). Average Fulton condition factor (Kn) of 1.15+0.09 (0.86-1.64). A wide range of GSI indicates that torpedo scads partially spawn at each month of the year.